Android App Inventor for the absolute beginner - Prayaga, Lakshmi; Hawthorne, Jeffrey; Whiteside, Alex. (Boston : Cengage Learning PTR, 2014)
Provides information on using the Android App Inventor to create mobile applications, covering such topics as sounds and images, animation, sensors, and multiple screens.
Keywords: Android (Electronic resource).; Android (Electronic resource); Application software -- Development; Smartphones -- Programming; Tablet computers -- Programming; Application software -- Design; Smartphones -- Computer software; Tablet computers -- Computer software